Artificial illumination near rivers may alter bat-insect trophic interactions. (September 2019) - Russo, Danilo; Cosentino, Francesca; Festa, Francesca; De Benedetta, Flavia; Pejic, Branka; Cerretti, Pierfilippo; Ancillotto, Leonardo
Abstract: Artificial illumination at night represents an increasingly concerning threat to ecosystems worldwide, altering persistence, behaviour, physiology and fitness of many organisms and their mutual interactions, in the long-term affecting ecosystem functioning. Bats are very sensitive to artificial light at night because they are obligate nocturnal and feed on insects which are often also responsive to lights. Here we tested the effects of LED lighting on prey-predator interactions at riverine ecosystems, using bats and their insect prey as models, and compared bat and insect reactions in terms of bat activity and prey insect abundance and diversity, respectively, on artificially lit vs. unlit nights. Artificial light influenced both insect and bat assemblages in taxon-specific directions: insect abundances increased at lit sites, particularly due to an increase in small dipterans near the light source. Composition of insect assemblages also differed significantly between lit and unlit sites. Total bat activity declined at lit sites, but this change was mainly due to the response of the most abundant species, Myotis daubentonii, while opportunistic species showed no reaction or even an opposite pattern ( Pipistrellus kuhlii ). We show that artificial lighting along rivers may affect trophic interactions between bats and insects, resulting in a profound alteration of community structure and dynamics. Graphical abstract: Image 1 Highlights: Artificial lighting may fragment watercourses putting an obstacle to bat movement. Photopositive insects may fall victim to light-tolerant bats along lit rivers. Light-averse bats reduce activity as a direct effect of lighting, not prey decrease. Lighting is widespread along rivers and may alter ecosystem services bats provide.